Backyard sounds: an immersive sound experience in Almenara-Vale do Jequitinhonha, Brazil - Rocha, Rosimária (2021)
This article is a study on the immersive sound installation “Backyard Sounds”. The union of our artistic practice to theoretical research resulted on the birth of this project. One of the main objectives of “Backyard Sounds” was the consideration of the sounds of contemporaneity. Seeking to lead users to experience videos and sounds in a dark room, since sounds were only set off with the users’ approach,sounds of nature and those produced by humans were used intentionally to demonstrate the inherent paradoxes of contemporary life. This research consists of a study on the immersive sound installation “Backyard Sounds”. The authors approach the artistic process involved in its creation and the concepts, notions, and reflections related to the computational artifact. The sounds heard were reveries of the soundscapes (concept of sounds of nature and others produced by humans), and it was intended to bring users the extreme paradoxes of contemporary life.